Cost effectiveness of patellofemoral versus total knee arthroplasty in younger patients. (August 2017) - Chawla, H.; Nwachukwu, B. U.; van der List, J. P.; Eggman, A. A.; Pearle, A. D.; Ghomrawi, H. M.
Abstract : Aims: Patellofemoral arthroplasty (PFA) has experienced significant improvements in implant survivorship with second generation designs. This has renewed interest in PFA as an alternative to total knee arthroplasty (TKA) for younger active patients with isolated patellofemoral osteoarthritis (PF OA). We analysed the cost-effectiveness of PFA versus TKA for the management of isolated PF OA in the United States-based population. Patients and Methods: We used a Markov transition state model to compare cost-effectiveness between PFA and TKA. Simulated patients were aged 60 (base case) and 50 years. Lifetime costs (2015 United States dollars), quality-adjusted life year (QALY) gains and incremental cost-effectiveness ratio (ICER) were calculated from a healthcare payer perspective. Annual rates of revision were derived from the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man. Deterministic and probabilistic sensitivity analysis was performed for all parameters against a $50 000/QALY willingness to pay. Results: PFA was more expensive ($49 811 versus $46 632) but more effective (14.3 QALYs versus 13.3 QALYs) over a lifetime horizon. The ICER associated with the additional effectiveness of PFA was $3097. The model was mainly sensitive to utility values, with PFA remaining cost-effective when its utility exceeded that of TKA by at least 1.0%. PFA provided incremental benefits at no increased cost when annual rates of revision decreased by 24.5%. Conclusions: Recent improvements in rates of implant of survival have made PFA an economically beneficial joint-preserving procedure in younger patients, delaying TKA until implant failure or tibiofemoral OA progression. The present study quantified the minimum required marginal benefit for PFA to be cost-effective compared with TKA and identified survivorship targets for PFA to become both less expensive and more effective. These benchmarks might be used to assess clinical outcomes of PFA from an economic standpoint within the United States healthcare system. Cite this article: Bone Joint J 2017;99-B:1028–36.